Association between food insecurity and anemia among women of reproductive age - Ghose, Bishwajit; Tang, Shangfeng; Yaya, Sanni; Feng, Zhanchun (PeerJ, 2016)
Background: Food insecurity and hidden hunger (micronutrient deficiency) affect about two billion people globally. Household food insecurity (HFI) has been shown to be associated with one or multiple micronutrient (MMN) deficiencies among women and children. Chronic food insecurity leads to various deficiency disorders, among which anemia stands out as the most prevalent one. As a high malnutrition prevalent country, Bangladesh has one of the highest rates of anemia among all Asian countries. In this study, we wanted to investigate for any association exists between HFI and anemia among women of reproductive age in Bangladesh. Methodology: Information about demographics, socioeconomic and anemia status on 5,666 married women ageing between 13 and 40 years were collected from a nationally representative cross-sectional survey Bangladesh Demographic and Health Survey (BDHS 2011). Food security was measured by the Household Food Insecurity Access Scale (HFIAS). Capillary hemoglobin concentration (Hb) measured by HemoCue® was used as the biomarker of anemia. Data were analysed using cross-tabulation, chi-square tests and multiple logistic regression methods. Results: Anemia prevalence was 41.7%. Logistic regression showed statistically significant association with anemia and type of residency (p = 0.459; OR = 0.953, 95%CI = 0.840–1.082), wealth status (Poorest: p < 0.001; OR = 1.369, 95%CI = 1.176–1.594; and average: p = 0.030; 95%CI = 1.017–1.398), educational attainment (p < 0.001; OR = 1.276, 95%CI = 1.132–1.439) and household food insecurity (p < 0.001; 95%CI = 1.348–1.830). Women who reported food insecurity were about 1.6 times more likely to suffer from anemia compared to their food secure counterparts. Conclusion: HFI is a significant predictor of anemia among women of reproductive age in Bangladesh. Programs targeting HFI could prove beneficial for anemia reduction strategies. Gender aspects of food and nutrition insecurity should be taken into consideration in designing national anemia prevention frameworks.
Keywords: Women; Anemia; Bangladesh; Micronutrient deficiency; Food insecurity